Que justiça é essa? Aspectos teórico-metodológicos da investigação de representações discursivas da justiça em acórdãos de habeas corpus e cartas do leitor - Bortoluzzi, Valeria Iensen (2008)
Life in society becomes possible because social beings share representations of the world and reality in which they live through the interactions of actors in a diversity of social practices. Some of the representations built in social contexts end up organizing society itself, becoming essential for human social life. The justice representations are an example. In this sense, by understanding how people represent justice in their daily lives, we understand part of the dynamics of relations that are established between individuals and institutions, and reflect the potential of change and stabilization of those representations in our society. The objectives of this thesis are: a) to investigate the representations of justice which emerge from social interactions in specific cultural contexts; b) to discuss the potential of change and/or stabilization of those representations of justice in our society; and c) to propose an interdisciplinary method of investigation-discussion of social representations. The epistemological methodology used here is the Depth Hermeneutics, proposed by Thompson (1995), which presupposed three stages of analysis: sociohistorical, realized with the support of Theory of Structuration and of Social Psychology; formal/discursive, realized through Systemic-Functional Linguistics (van Leeuwen taxonomy); and interpretation/re-interpretation, realized by Critical Discourse Analysis. To investigate justice representations, we used 470 jurisprudence of habeas corpus produced by the Brazilian Supreme Court, in 2005, and 66 readers letters which had the word justice and its derivations, published in 2005 by Veja magazine. The texts were electronically processed in search for the word justice and its derivations, which were analyzed to identify the meaning construed in the immediate context of occurrence and in the wider context of the phrase or text. In this phase of the study, three forms of representations were identified: justice as principle, justice as goods and services, and justice as institution. Secondly, we analyzed the occurrence of those representations, in order to identify the representation which is recurrent in society. We established that the most recurrent representation in the speeches and social discourses is the justice as institution. This recurrence has the objective to delimit the action spaces and responsibilities, as well as to legitimate a highly unstable representation with a huge potential of change. The justice as institution that we have today can be destructured and restructured in a short or long-term future, as it is on the mercy of social changes. The justice as principle is also very recurrent in the social body. However, in its essence, it is a high stable representation, as the terms of the agreement are changed but not the agreement itself. Literature shows that this representation is the oldest and data shows that it is the most present in society. The stability or the potential of change of justice as good and services, the less recurrent in the corpus, depend on social body and institutions. As long as the social body and institutions legitimate the set of laws and regulations which constitute representation today, it will not change.